Peran Pendidikan Agama Islam dalam Membentuk Karakter Generasi Z di Era Digital - Delia Rahmi; Putri Mauliani Akmal; Yulia Rizki; Muhammad Rifai Harahap (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The rapid development of information and communication technology in the digital era has brought massive disruptions to all aspects of human life, including the educational paradigm and societal morality. Generation Z, as digital natives who grow up alongside these technological advancements, faces significant vulnerabilities regarding character degradation and moral decadence due to boundless exposure to global information. This research aims to critically analyze the strategic role of Islamic Religious Education in shaping and fortifying the character of Generation Z amidst the complexities of the digital landscape. The method used in this study is a qualitative literature review, which systematically synthesizes and analyzes twenty relevant academic sources. The findings indicate that Islamic Religious Education serves as an irreplaceable moral compass by internalizing the fundamental values of Tawhid and prophetic ethics. Furthermore, the integration of modern digital pedagogy with classical Islamic traditions, accompanied by the teacher's role as a moral exemplar (mu'addib), is crucial for effective character building. In conclusion, a collaborative educational ecosystem involving the family, school, and society is mandatory to ensure the continuous moral resilience of the younger generation in facing future technological disruptions.